MUSCULOSKELETAL DISORDER COMPLAINTS AMONG WELDERS AND GRINDING WORKERS AT PT. X: MUSCULOSKELETAL DISORDER - Sugiantoro, Sugiantoro; Ratriwardhani, Ratna Ayu; Sahri, Moch.; Sunaryo, Merry (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Welders and grinding work at PT. X is carried out manually with non-ergonomic working postures, such as bending or prolonged standing. This study aims to describe work-related musculoskeletal disorder (MSDs) complaints based on individual characteristics (age, gender) and job-related factors (length of employment, daily working hours, and type of work). Methods: The method used is a descriptive quantitative approach with a cross-sectional design, involving 47 respondents using a total population sampling technique. Data were collected using a musculoskeletal complaint survey instrument based on the Indonesian National Standard (SNI) 9011:2021. Results: The results showed that the majority of respondents were male (93%), aged 25-34 years (42%), and had 1-5 years of work experience (70%). The most reported MSDs complaints were in the lower back (36%), upper back (55%), and neck (23%). Conclusion: Based on the descriptive analysis, both individual and occupational factors contributed to MSDs complaints, particularly in body parts affected by non-ergonomic working postures. Recommended interventions include proper posture training, provision of ergonomic aids to reduce physical load, and regular health check-ups to decrease the prevalence of MSDs among workers.